2015
DOI: 10.1002/apj.1900
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of disaccharides containing two glucose units in subcritical water

Abstract: Disaccharides containing two glucose units, including trehalose, cellobiose, maltose, gentiobiose, and isomaltose, were hydrolyzed in a single-component system using subcritical water at 200-240°C and 10 MPa. A mixture of maltose and trehalose was also hydrolyzed in a binary-component system using subcritical water at 210 and 230°C. The fraction of the remaining disaccharides decreased as a function of the residence time and could be expressed by the Weilbull equation at any temperature. While trehalose showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The glycosidic scission of carbohydrates was mainly attributed to the • OH radical-driven hydrogen atom transfer reaction, which was closely correlated with the electrostatic potential charge of the glycosidic oxygen atom . Thus, the electron density around the glycosidic oxygen atom could be used to indicate the lability of glycosidic bonds . For example, in the optimized structures of different disaccharides (Figure S13), the molecular conformations of sucrose, turanose, and maltose were more condensed than those of other disaccharides, resulting in a greater difficulty for the hydrogen atom transfer process near the glycosidic linkage.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The glycosidic scission of carbohydrates was mainly attributed to the • OH radical-driven hydrogen atom transfer reaction, which was closely correlated with the electrostatic potential charge of the glycosidic oxygen atom . Thus, the electron density around the glycosidic oxygen atom could be used to indicate the lability of glycosidic bonds . For example, in the optimized structures of different disaccharides (Figure S13), the molecular conformations of sucrose, turanose, and maltose were more condensed than those of other disaccharides, resulting in a greater difficulty for the hydrogen atom transfer process near the glycosidic linkage.…”
Section: Resultsmentioning
confidence: 99%
“…This was because the energy barrier for abstracting C 1 -centered hydrogen atoms by • OH radical correlated to the electron density around the glycosidic oxygen atom. 24 As shown in Figure S13, the glycosidic C 1 −O bond length of cellobiose was 1.388 Å, which was significantly shorter than that of other disaccharides and provided more negative attraction for the C 1 -centered hydrogen atom. Dai, et.al., (2017) found that in the • OH radical-induced degradation of sucrose, the energy barriers for abstracting a hydrogen atom from the C−H bond outside of the pyranose and furanose rings were much lower than those from the C−H bond on two rings.…”
Section: Analysis Of Degradation Mechanismsmentioning
confidence: 97%
See 3 more Smart Citations